THE EFFECT OF TRUNK MUSCLE EXERCISE ON REDUCING THE RISK OF FALLING IN THE ELDERLY - Siti Sarah Bintang Sarah Bintang; Titin Novayanti Dey; Timbul Siahaan; Redi T Siahaan (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
The biological aging process causes the elderly to experience a decline in physical function such as postural disorders and changes in walking style that make the elderly vulnerable to falls. The purpose of this study is to find out if trunk muscle exercise has an effect on reducing the risk of falling elderly, and to know the risk of falling elderly before and after trunk muscle exercise treatment. The research population is all elderly in the Medical Rehabilitation Installation of Raden Mattaher Jambi Hospital which is at risk of falling by 18 people. The study sample was seniors aged 60-65 years who met the inclusion criteria of 12 people. Given trunk muscle exercise treatment supervised 3 times a week for 2 weeks. The measuring instrument in this study used Timed Up and Go Test. Data analysis using Simple Paired T Test with a confidence level of 95%. Based on the analysis obtained the average risk of elderly fall in Hospital RD Mattaher before treatment is 13.92 and the average risk of falling after treatment is 7.42. There is a significant influence of trunk muscle exercise on the decrease in the risk of falling elderly with p value = 0.000. It is recommended that the elderly continue the exercise program to maintain endurance.